THE INFLUENCE OF SELLING PRICE, SERVICE QUALITY AND PRODUCT QUALITY ON CONSUMER SATISFACTION (CASE STUDY AT THE MIRAH GROCERY STORE, AT PURWODADI CITY) - Arneta Karenina Ardani; Winarsih (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2024)
Background & Aim: The success of a company is not only measured by the number of consumers who buy products or services, but also by the company's ability to maintain consumer satisfaction The Mirah grocery store in Purwodadi faces stiff competition from similar retail stores. This research focuses on how the factors of selling price, service quality, and product quality affect customer satisfaction which is very important to retain customers and win business competition in Indonesia which is getting tougher. Methods: The method used is a quantitative approach with data collection through questionnaires distributed to 160 respondents. Data analysis was carried out using multiple linear regression to test the effect of each variable on customer satisfaction. Results: The results showed that selling price, service quality, and product quality have a positive and significant influence on customer satisfaction. Simultaneously, the three variables contribute to increasing customer satisfaction, with service quality being the most dominant factor. The conclusion of this study is that companies need to pay attention to these three factors to increase customer satisfaction and maintain customer loyalty. This research is expected to provide insight for retail store owners in formulating more effective marketing strategies. Conclusion & Suggestion: Selling price, service quality and product quality are important elements in increasing consumer satisfaction. However, there are certain things that need to be paid attention to. This research serves as a foundational study, and future research must be further developed regarding the development of methods and confirming the relationship between variables,especially understanding correctly regarding the moderating variables in the research to be carried out. It is also recommended to add other variables